Unveiling the Provenance - Tina Berdajs (Asian Studies)
This paper offers an insight into the earliest museum donations of East Asian objects in the area of present-day Slovenia. A special focus is given to the donations of porcelain by noblewomen donors in the first half of the 19th century, notably in the year 1833. It expands on their backgrounds and biographies, as well as tries to determine the circumstances in which they acquired and were able to donate or bequest Japanese and Chinese porcelain (and in some cases other ceramics of East Asian origin) to museum collections. The earliest donations are presented through in-depth studies of Illyrisches Blatt, a weekly supplement to the paper Laibacher Zeitung, where, in the first half of the 19th century, all donations to the Provincial Museum of Carniola (Krainisches Landesmuseum; today the National Museum of Slovenia) were recorded. Through the identification of Asian objects and donors, a curious situation relating to several woman donors of East Asian porcelain is uncovered. The paper also presents these donors and offers an analysis of the objects they donated.